Aetiology of perforating eye injury. Issue 5 (May 1993) - Luff, A J; Hodgkins, P R; Baxter, R J; Morrell, A J; Calder, I
Abstract : This study addresses the aetiology of perforating ocular injury in childhood and possible preventive measures. Data have been collected from the case notes of 143 patients presenting over a 10 year period to a single ophthalmic unit. Injuries occurred most often in a domestic setting (34%) or with a child at play (19%) and showed an overall four to one ratio of boys to girls. Sports injuries accounted for 15% and assault for 8% of all injuries. A changing pattern of ocular injury is evident: road traffic accidents constituted 6% of injuries, compared with 31% in a similar study published in 1976. The role of litigation is discussed, particularly with regard to firearms, which accounted for 8% of injuries. It is concluded that the most important factor in the prevention of perforating ocular trauma is parental awareness, 53% of injuries occurring with the child in a domestic setting or at play.